2020
DOI: 10.1080/11745398.2020.1859391
|View full text |Cite
|
Sign up to set email alerts
|

The right to the city: outdoor informal sport and urban belonging in multicultural spaces

Abstract: The right to the city: outdoor informal sport and urban belonging in multicultural spacesThe right to the city: outdoor informal sport and urban belonging in multicultural spaces Studies on 'everyday multiculturalism' and 'lived multiculture' have advanced knowledge on the kinds of inclusive everyday spaces and practices that characterise our culturally complex, mobile and superdiverse cities. This paper expands this agenda by exploring informal sporting and leisure interactions amongst migrant and ethnically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Participants in this study provided rich insight into the deep structural and systemic inequities that continue to marginalize and exclude refugee-background communities from participation in community-based physical activity programs. It is important to consider the significance of these barriers in the context of contemporary findings that participation in such programs plays a key role in democratizing cities and facilitating broader civic participation and can thus be understood as a fundamental right to and in place ( Aquino et al ., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Participants in this study provided rich insight into the deep structural and systemic inequities that continue to marginalize and exclude refugee-background communities from participation in community-based physical activity programs. It is important to consider the significance of these barriers in the context of contemporary findings that participation in such programs plays a key role in democratizing cities and facilitating broader civic participation and can thus be understood as a fundamental right to and in place ( Aquino et al ., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…While recognising the possibility of generative interactions, the potential for relations of ambivalence and exclusion have also been noted (Valentine 2008, Skrbis andWoodward 2007). In this body of work, the socio-material dimensions of placesas part of an assemblage of human and non-human elements that make up the city-feature strongly in the analysis of intercultural encounters in ordinary contact zones or other transversal places (for example, public libraries, sports fields or backyards) (Amin 2012, Neal et al 2019, Wise 2009, Fincher and Iveson 2008, Aquino et al 2020.…”
Section: Migration Neoliberal Globalisation and Placementioning
confidence: 97%
“…In a study from the same area, Figari, Haaland and Krange (2009) found that walking in the neighbourhood was an important mode of exercise for immigrant women, both as a social activity and alone. Aquino et al (2020) found that playing sports in public areas helps migrants generate a sense of belonging in Singapore, though the social exclusion migrants experience in the city extends to some extent to the sports in these public areas.…”
Section: North and West Country Participants Logged Fewest Sport-related Locationsmentioning
confidence: 98%